2016
DOI: 10.1038/srep23120
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-10a derived from amniotic fluid stem cells preserves ovarian follicles after chemotherapy

Abstract: Chemotherapy (CTx)-induced premature ovarian failure (POF) in woman remains clinically irreversible. Amniotic fluid stem cells (AFSCs) have shown the potential to treat CTx-induced POF; however, the underlying mechanism is unclear. Here we demonstrate that AFSC-derived exosomes recapitulate the anti-apoptotic effect of AFSCs on CTx-damaged granulosa cells (GCs), which are vital for the growth of ovarian follicles. AFSC-derived exosomes prevent ovarian follicular atresia in CTx-treated mice via the delivery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
115
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 59 publications
5
115
1
2
Order By: Relevance
“…Our results showed that the EMVs present in CM are positive for surface mesenchymal antigens CD 90 and CD 29 and exosome related protein CD63. The vesicles are a mixed population of exosomes and shedding vesicles4041. Indeed, in our study the fluorescence microscopic analyses revealed that the isolated EMVs show spherical morphology associated to a different size in both healthy and disease specific cells.…”
Section: Discussionmentioning
confidence: 51%
“…Our results showed that the EMVs present in CM are positive for surface mesenchymal antigens CD 90 and CD 29 and exosome related protein CD63. The vesicles are a mixed population of exosomes and shedding vesicles4041. Indeed, in our study the fluorescence microscopic analyses revealed that the isolated EMVs show spherical morphology associated to a different size in both healthy and disease specific cells.…”
Section: Discussionmentioning
confidence: 51%
“…In this study, Bim expression was post‐transcriptionally modulated by miR‐17 and miR‐106b . Of the miRNAs we tested, miR10a , miR‐17 , and miR‐24–1 have been shown to regulate Bim expression in other organ systems: cardiac myocytes (5355), pancreatic carcinoma (99), ovarian cells (52), lymphocytes (100, 101), or acute lymphocytic leukemia (56). Contrary to our findings, Kan and colleagues (57) did not detect changes in Bim expression in the presence of either the miR‐106b mimic or the miR‐106b inhibitor, probably because of differences in endogenous miRNA expression in different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of MSCs as cell therapy for the treatment of POF has been investigated in many studies. MSCs from various sources have been used for this purpose, and it has been found that these cells have different abilities in improving ovarian function (Fu, He, Xie, & Liu, ; Song et al, ; Sun et al, ; Xiao et al, ). In a previous study, a successful treatment of POF mice using MSC transplantation was reported (Lai et al, ; Liu et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%